Electromagnetic wave absorbing performance of aspirin powder during 2450 MHz microwave drying. Issue 5 (26th March 2021) - Zhang, Fucheng; Zhai, Di; Shang, Xiaobiao; Chen, Junruo; Liu, Meihong; Peng, Jinhui
Abstract: The absorbing performance of pharmaceutical powders has an important effect on the efficiency of microwave drying. In this study, in order to achieve optimal microwave absorption, the reflection loss (RL) of aspirin powder is calculated based on the theory of electromagnetic wave transmission line under different temperatures, moisture contents, microwave incident angles and polarization modes. In addition, the effect of the dielectric-assisted absorbing layer (SiC ceramics) on the microwave absorbing performance of aspirin powder (weak absorbing materials) with low moisture content is analyzed. The results show that the RL curve of aspirin powder fluctuates with increasing thickness; several absorption peaks appear, and the absorption peaks shift to smaller thicknesses as the temperature and moisture content increase. The RL of aspirin powder in the transverse electric polarization mode decreases monotonically as the incident angles increase. The effect of Brewster's angle causes the RL of aspirin powder in the transverse magnetic polarization mode to first decrease and then increase with the increasing incident angle, and an absorption peak occurs. However, the RLs of both polarization modes are close to zero at 90°. The use of SiC ceramics as the susceptor can reduce the RL of the double-layer absorber and widen the aspirin powder thickness interval for an RL below −20 dB. This research can help to optimize the microwave drying process parameters of pharmaceutical powders and the design of microwave drying equipment.